THE ROLE OF STAKEHOLDERS IN LEGAL IN SERVICES AT CLASS I SURAKARTA STATE DETENTION CENTER - Pisstama, Oka Putra Mita; Pangestuti, Naniek (Universitas Nusa Cendana, 2025)
This study aims to describe the role of stakeholders in legal aid services at the Surakarta Class I State Detention Center, with a focus on the involvement of internal and external parties, such as the Mawar Saron Legal Aid Institute. A descriptive qualitative approach was used, with data collection through in-depth interviews, direct observation, and documentation studies, and analysis using NVivo12 Pro. The research used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation studies. The results showed that the role of each stakeholder is important in ensuring the quality of legal aid for detainees, although there are obstacles in its implementation, such as limited resources and fluctuations in the number of legal aid recipients. The researcher found that stakeholder engagement still needs to be improved, especially in terms of more effective communication and improved leadership at the level of the Head of Detention Center and Director of LBH Mawar Saron. The recommendations resulting from this research are the importance of strengthening cooperation between stakeholders and optimizing communication strategies to improve legal aid services in Surakarta Class I Detention Center. Keywords: Stakeholders; Legal Aid Services; State Detention Center; LBH Mawar Saron